The State of Open Data 2022: The longest-running longitudinal survey and analysis on open data - Hahnel, Mark; Smith, Graham; Hardeman, Megan (Septentrio Conference Series, 2022)
Open science is key to advancing discovery and furthering scientific progress for an accelerated and more effective research system. As proactive partners driving the transition to open science, Springer Nature and Figshare believe that research data should be open, accessible and reusable, to help speed up the pace of discovery and benefit society. As a member of UNESCO’s Global Open Science Partnership, Figshare works closely with other members of the open science community to inform and develop practices toward open data sharing. To better understand the current landscape, Springer Nature, Digital Science, and Figshare published the seventh annual State of Open Data report, based on over 5,000 responses from the global research community about motivations, challenges, perceptions, and behaviours toward open data. This poster will share the key findings from the report, including a focus on respondents’ preferences around open data policies, looking at mandates, requirements and grants, and the role that institutions, publishers and funders play.